HUBUNGAN ANTARA LINGKAR PINGGANGDENGANKADARHS-CRP SERUMPADA MAHASISWA OBES DAN TIDAK OBES DI FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Fatie, Anita Ohe S.; Bolang, Alexander S. L.; Mayulu, Nelly (e-Biomedik, 2014)
Abstract: The rapid socioeconomic growth has led to a more sedentary lifestyle and change in diet over the past several decades. As a result of prosperity,obesity has become an important health problem. And then problem healthnutrition world, both in developed countries and in developing countries. Waist circumference more than normal is one component in the metabolic syndrome. An increased incidence of metabolic syndrome in line with the increase in obesity. Hs-CRP is a protein in the synthesis in the liver in response to inflammatory stimuli during the acute phase. This research was conducted to find out the waist circumference and hs-CRP levels in students faculty of medicine University of Sam Ratulangi Manado. And the type of research used is the observational approach cross sectional analytic. Results anasis statistics by using test mann whitney u showed there are different meaning ( p = 0.00 ( 0,00 ). Based on the test spearmen statistics then obtained value a correlation coefficient ( r ) by 0.472 and value Ï = 0.000 < Î±= 0.05.. This shows there is a relationship between waist circumference with hs-CRP levels on students obese and not obese in medical schools university sam ratulangi manado. Keyword: waist circumference, hs-CRPÂ Â  Abstrak: Percepatan pertumbuhan sosial ekonomi menyebabkan orang lebih kurang bergerak dimana perubahan dalam pola diet dan yang terjadi pada beberapa dekade. Akibatnya obesitas menjadi masalah penting bagi kesehatan. Dan jugamasalahÂ  kesehatanÂ  Â Â gizimasyarakatdunia, baikdinegaramajumaupundinegara berkembang. Lingkar Pinggang yang besar dari normal adalah salah satu komponen dalam sindroma metabolik. Peningkatan kejadian sindroma metabolik sejalan dengan peningkatan obesitas.Hs-CRP merupakan protein yang di sintesis di hati sebagai respon terhadap rangsangan pada saat inflamasi fase akut.Penelitian ini dilakukan untuk mengetahui Lingkar Pinggang dan kadar hs-CRP pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado. Dan jenis penelitian yang dipakai adalah observasional analitik dengan pendekatan cross sectional. Hasil anasis statistik dengan menggunakan uji Mann Whitney U menunjukan terdapat perbedan bermakna (p=0.00(0,00). Berdasarkan hasil uji spearmen statistik maka didapatkan nilai koefisien korelasi (r) sebesar 0.472 dan nilai Ï = 0.000 < Î±= 0.05. Hal ini menunjukan terdapat hubungan antara lingkar pinggang dengan kadarÂ  hs-CRP pada mahasiswa obes dan tidak obes di Fakultas Kedokteran Universitas Sam Ratulangi Manado. Kata Kunci: Lingkar Pinggang, hs-CRP